(untitled) (Journal of EAHIL, 2019)
The paper aims to promote the knowledge of the extraordinary collection of anatomical subject drawings by Antonio Canova, the most important Italian neoclassic artist, owned by the National Institute of Health Library in Rome. The history of acquisition by the library and the analysis of their importance in the long career of the artist is also treated. A short story about the fortune of the drawings in the last 20 years completes the study.